2012
DOI: 10.1177/1079063212465900
|View full text |Cite
|
Sign up to set email alerts
|

Why Have All the Boys Gone? Gender Differences in Prosecution Acceptance of Child Sexual Abuse Cases

Abstract: Cases of child sexual abuse (CSA) referred to the District Attorney (DA) are not necessarily accepted for prosecution. Two pilot studies sought to investigate whether there were gender differences in whether cases of CSA referred to the DA's office were accepted by the DA and, if they existed, what might account for gender differences in decisions to accept cases and file charges. The results of the first study indicated that cases involving male victims were significantly less likely to be accepted for prosec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
3
13
1
1
Order By: Relevance
“…Recent years have seen a gradual expansion of the literature on male victims of child sexual abuse in general (see, e.g., Alaggia, 2005;Cashmore and Shackel, 2014;Edelson, 2012;Homma et al, 2012;Priebe and Svedin, 2009;Scrandis and Watt, 2014). Nonetheless, in a recent rapid evidence assessment around child sexual abuse/exploitation, most of the 184 studies covered were found to focus exclusively or overwhelmingly on female victims (Brayley, Cockbain & Gibson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen a gradual expansion of the literature on male victims of child sexual abuse in general (see, e.g., Alaggia, 2005;Cashmore and Shackel, 2014;Edelson, 2012;Homma et al, 2012;Priebe and Svedin, 2009;Scrandis and Watt, 2014). Nonetheless, in a recent rapid evidence assessment around child sexual abuse/exploitation, most of the 184 studies covered were found to focus exclusively or overwhelmingly on female victims (Brayley, Cockbain & Gibson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with males, females are more often reported victims of CSA (e.g., Priebe & Svedin, 2008), make more CSA allegations (e.g., Hershkowitz, Lamb, & Katz, 2014), and are more likely to have their allegations sent to district attornies for prosecution (Edelson, 2013). Females are also more likely than males to be believed when reporting CSA histories (e.g., Haegerich & Bottoms, 2000).…”
Section: Child Gendermentioning
confidence: 98%
“…Given that female CSA victim cases are more often prosecuted successfully than are male CSA cases (Edelson, 2013) and females are more often believed than males when they report CSA (e.g., Eisenberg, Owens, & Dewey, 1987;Haegerich & Bottoms, 2000), we predicted that female victims would match adults' expectations of a typical CSA victim, and, as a result, female victims would be rated as more credible than male victims (e.g., Nunez et al, 2011), and garner greater confidence in guilt ratings. However, victim gender, like victim age, was not associated with current perceptions of child credibility or guilt.…”
Section: Child Age and Gendermentioning
confidence: 98%
“…Although gender is unrelated to risk for most forms of maltreatment, girls are at much higher risk of sexual abuse than are boys (though certainly boys are not immune from this form of abuse). As such when considering children in criminal cases, more girls than boys have contact (Edelson, 2013 ;Finkelhor, 1994 ;Walker, Carey, Mohr, Stein, & Seedat, 2004 ). In the dependency system, gender is more evenly distributed.…”
Section: Child Participants In Legal Casesmentioning
confidence: 99%